2011
DOI: 10.1590/s1806-37132011000100017
|View full text |Cite
|
Sign up to set email alerts
|

O tabagismo e a mulher: riscos, impactos e desafios

Abstract: The initiative was motivated by mounting evidence that smoking in this population group had increased in many countries.(1,2) Even in societies where smoking has decreased, the reduction is less pronounced among women. (1,4) It is known that the tobacco industry makes an effort to increase the numbers of women who are nicotine-dependent. Data regarding 151 countries revealed that, in general, the prevalence of smoking is higher in adolescent boys than in adolescent girls (12% vs. 7%); however, in various count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
28

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 43 publications
2
20
0
28
Order By: Relevance
“…In a review article, Lombardi et al 59 showed an extensive approach on smoking in the female sex, from aspects associated with motivations for initiation, addiction -usually higher in females -epidemiological data on smoking, tobaccorelated diseases, calling attention to its influence on breast cancer, which, from a controversial theme until a few years ago, came to be included among the tobacco-associated cancers, as well as aspects related to treatment.…”
Section: Smoking and The Female Sexmentioning
confidence: 99%
“…In a review article, Lombardi et al 59 showed an extensive approach on smoking in the female sex, from aspects associated with motivations for initiation, addiction -usually higher in females -epidemiological data on smoking, tobaccorelated diseases, calling attention to its influence on breast cancer, which, from a controversial theme until a few years ago, came to be included among the tobacco-associated cancers, as well as aspects related to treatment.…”
Section: Smoking and The Female Sexmentioning
confidence: 99%
“…12 A prevalência de tabagistas do sexo feminino, em análise feita nas capitais brasileiras em 2010, é de 12,4%. 13 dos entrevistados afirmaram já terem participado de alguma forma no controle do tabagismo.…”
Section: Discussionunclassified
“…Devido a este fato, as instituições e os profissionais de saúde estão tendo uma maior atenção com o público feminino (LOMBARDI et al, 2011). Segundo Borges e Barbosa (2009), 500 mil mulheres vão a óbito por ano em decorrência do tabagismo, fato que se encontra em ascensão em todos os países.…”
Section: Sobre O Tabagismounclassified